Achieving Quasi-Complete Balance in U-shaped Assembly Lines Using Idle Time Elimination Methodologies - Zening Wu; Wenqian Luo (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2025)
The problem of balancing the U-shaped production line is a well-known NP-problem in mass production, where the main objective is to allocate tasks efficiently to the workstations while minimising idle time and balancing the workload throughout the production line. The study introduces two new methods to address these issues and increase the efficiency of line balancing: Operators Arrangement for U-shaped line Balancing (OAUB) and Layout Design for U-shaped line Balancing (LDUB). OAUB optimizes the allocation of workers by strategically adjusting the assignment of tasks, ensuring that idle time is minimised and that the use of workers is maximised. By contrast, LDUB alleviates idle time by filling in the gaps between tasks with independent, low-processing tasks from non-critical paths, thus ensuring a more efficient use of available time during the transitions. Implementation of these methods has shown promising results and significantly reduced the idle time of the production processes. Specifically, OAUB achieved a reduction of only 0.9 units of idle time, while LDUB decreased idle time by 3 units. These results are particularly important from a sustainability point of view, as they contribute to reducing waste through better use of resources and increased production efficiency. Unlike traditional approaches, which are mainly focused on minimizing the number of workstations or the reduction of cycle times, our methodology provides a more integrated approach to balancing the workload between workstations. The practical implications of these methods are significant as they are applicable to the real-world production environment and offer effective and efficient solutions to achieve near complete alignment on U-shaped assembly lines, thus improving overall productivity and sustainability in an environment of mass production.